Multisensory interactions in the depth plane in front and rear space: A review. - Van der Stoep, N; Nijboer, T; Van der Stigchel, S; Spence, C (Elsevier, 2015)
In this review, we evaluate the neurophysiological, neuropsychological, and psychophysical evidence relevant to the claim that multisensory information is processed differently depending on the region of space in which it happens to be presented. We discuss how the majority of studies of multisensory interactions in the depth plane that have been conducted to date have focused on visuotactile and audiotactile interactions in frontal peripersonal space and underline the importance of such multisensory interactions in defining peripersonal space. Based on our review of studies of multisensory interactions in depth, we question the extent to which peri- and extra-personal space (both frontal and rear) are characterized by differences in multisensory interactions (as evidenced by multisensory stimuli producing a different behavioral outcome as compared to unisensory stimulation). In addition to providing an overview of studies of multisensory interactions in different regions of space, our goal in writing this review has been to demonstrate that the various kinds of multisensory interactions that have been documented may follow very similar organizing principles. Multisensory interactions in depth that involve tactile stimuli are constrained by the fact that such stimuli typically need to contact the skin surface. Therefore, depth-related preferences of multisensory interactions involving touch can largely be explained in terms of their spatial alignment in depth and their alignment with the body. As yet, no such depth-related asymmetry has been observed in the case of audiovisual interactions. We therefore suggest that the spatial boundary of peripersonal space and the enhanced audiotactile and visuotactile interactions that occur in peripersonal space can be explained in terms of the particular spatial alignment of stimuli from different modalities with the body and that they likely reflect the result of prior multisensory experience.